Evaluation of Solar Dryer Use in Corn Drying Process in Aur Serumpun Farmer Group, Simpang Village, Pasaman Regency - Syukri, Daimon; Yanti, Nika Rahma; Salim, Emil; Laimnimitr, Napassawan (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Corn drying is a crucial process in maintaining the quality of the harvest and reducing the risk of contamination by fungi. Traditional drying methods that rely on sunlight often have constraints on efficiency and quality of results. Solar dryer technology is present as an innovative solution that is more effective and environmentally friendly. This activity aims to evaluate the effectiveness of solar dryers in the corn drying process in Aur Serumpun Farmer Group, Simpang Village, Pasaman Regency. Evaluation methods include measuring water content before and after drying, time efficiency analysis, and farmer satisfaction surveys. The results of the activity showed that solar dryers were able to reduce the water content of corn to <14% in a shorter time compared to conventional methods. In addition, farmers reported labor efficiency and improved crop quality. Thus, solar dryers can be adopted as an alternative technology to improve agricultural productivity and sustainability